Quality of fresh-cut apples as affected by dip wash treatments with organic acids and acidic electrolyzed water - PLESOIANU,Alina M. (2022)
Abstract The objective of this study was to investigate the effects of dipping in solutions of citric (2%), benzoic (0.2%), sorbic (0.2%) and ascorbic (0.5%) acids and in acidic electrolyzed water on the quality attributes and surface microbiota of fresh-cut apples, cvs ‘Florina’ and ‘Ionathan’, packaged in disposable plastic containers under normal atmospheric conditions during 14 days storage at 8 °C. The colour, firmness, total phenolic content, antioxidant activity and surface microbial load were determined weekly throughout storage. The colour results indicated that acidic electrolyzed water reduced browning while the ascorbic and citric acids were less effective in controlling the enzymatic browning of fresh-cut apples. After 14 days of refrigerated storage, the samples treated with 2% citric acid and acidic electrolyzed water maintained significantly higher firmness, total phenolic content and antioxidant activity than the other treated and control samples. The microbiological analysis revealed that organic acids successfully suppressed bacterial growth throughout the storage period as compared to the control samples. The sorbic and benzoic acids at 0.2% were also effective on yeasts but these dip treatments determined a higher darkening, yellowing and loss of firmness and of antioxidant activity during storage.